Real-Time Remote Control of Artificial Cilia Actuation Using Fingertip Drawing for Efficient Micromixing. (October 2014) - Chen, Chia-Yuan; Yao, Chih-Yuan; Lin, Cheng-Yi; Hung, Shih-Hsuan
Low-efficiency diffusion mechanism poses a significant barrier to the enhancement of micromixing efficiency in microfluidics. Actuating artificial cilia to increase the contact area of two flow streams during micromixing provides a promising alternative to enhance the mixing performance. Real-time adjustment of beating behavior in artificial cilia is necessary to accommodate various biological/chemical reagents with different hydrodynamic properties that are processed in a single microfluidic platform during micromixing. Equipping the microfluidic device with a self-troubleshooting feature for the end user, such as a bubble removal function during the process of multiple chemical solution injections, is also essential for robust micromixing. To meet these requirements, we initiated a new beating control concept by controlling the beating behavior of the artificial cilia through remote and simultaneous actuation of human fingertip drawing. A series of micromixing test cases under extreme flow conditions ( Re < 10 –3 ) was conducted in the designed micromixer with high mixing performance. Satisfactory micromixing efficiency was achieved even with a rapid beating trajectory of the artificial cilia actuated through the fingertip motion of end users. The analytical paradigm and results allow end users to troubleshoot technical difficulties encountered during micromixing operations.